Study on the Key Competencies Framework for Arts Education Professionals - Dong, YanJun; Han , YingXiong (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: Cultivating the key competencies of university students has become an unavoidable trend and responsibility for universities, which is not only in line with the overall development trend of the world, but also in line with the practical needs of the development of higher education. From the current situation of the research on the key competencies of art education professionals, there is a lack of a key competencies framework for art education professionals that is based on the concept of outcome-based education and constructed around learning outcomes. Materials and Methods: This study employs a mixed research methodology. Qualitative data were sourced from relevant literature and processed using textual analysis methods. Quantitative data were collected through a questionnaire survey, and the data processing involved conducting reliability and validity analysis, exploratory and confirmatory factor analysis, as well as descriptive statistics, using SPSS, STATA and AMOS software. Results: The study finds that the framework of key competencies for art education professionals consists of nine key competencies learning outcome across three dimensions: technical intelligences, emotional intelligences & analytical creative intelligences and personal intelligences. In the technical intelligences, six learning outcomes were selected: core academic content and skill of art, studio art, teaching competencies, academic support, communication and cooperation, information literacy. In the emotional intelligences & analytical creative intelligences，two learning outcomes were selected: attitudes and ethical understanding, decision-making skills and thinking ability. In the personal intelligences，one learning outcome was selected, which is desirable personal qualities. Conclusion: The key competencies framework for art education majors emphasizes a "top-down design" method that can serve as a tool for curriculum planning and evaluation, thereby facilitating the development of courses. Of course, art education majors need to conduct regular status surveys to optimize training objectives based on industry development and changes in employer demands, ensuring that students possess the skills and competencies that best meet market needs upon graduation. In addition to optimizing the training goals for art education professionals, institutions should also make students aware of these goals early on, helping them understand the key competencies required to become an art teacher. If students regularly self-check, self-regulate, and educate themselves against the requirements of key competencies for art teachers, they can narrow and bridge role gaps, making their role behavior gradually align with societal expectations and requirements. Through their efforts, they aim to achieve self-improvement and integrate their roles.